2006
DOI: 10.1111/j.1600-0447.2005.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a community‐based mental health service focusing on severe mental illness. The Verona experience

Abstract: Developing community-based mental health care requires a series of coordinated actions that need to be pursued over a long period of time. Service evaluation, including costs assessment, is an important part of this exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 14 publications
(12 reference statements)
1
36
0
3
Order By: Relevance
“…Higher costs resulted for patients with an ongoing episode, which one can relate to the profile of these patients, who were likely to have a more severe diagnosis, to be single, a resident in a psychiatric residential facility or sheltered accommodation and unemployed. These seem to be the most chronic patients, for whom, as described in Tansella et al (2006), resources are targeted by our community-based services to provide integrated interventions such as medication, family support and social care. Accordingly, the costs of their care are higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher costs resulted for patients with an ongoing episode, which one can relate to the profile of these patients, who were likely to have a more severe diagnosis, to be single, a resident in a psychiatric residential facility or sheltered accommodation and unemployed. These seem to be the most chronic patients, for whom, as described in Tansella et al (2006), resources are targeted by our community-based services to provide integrated interventions such as medication, family support and social care. Accordingly, the costs of their care are higher.…”
Section: Discussionmentioning
confidence: 99%
“…More information on the South Verona PCR and on the research setting can be found elsewhere (Tansella et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this paper was to study mortality, causes of death and associated risk factors among psychiatric patients followed up over a 20-year period in an area where psychiatric care is entirely provided by community-based psychiatric services and has been monitored by a case register since 1978 (Tansella et al 2006). This research allowed us to repeat the mortality analyses published in a previous study by Amaddeo et al (1995) conducted in South Verona for a time period of 10 years, on a sample followed up for a twofold longer period, also adding a detailed analysis of causes of death that was not possible to perform in our previous study because of the small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Esse modelo é definido com base em três componentes essenciais: a diminuição das admissões hospitalares pela provisão de serviços comunitários; a desospitalização, após preparação, de pacientes internados por longos períodos; a criação e manutenção de uma rede de serviços na comunidade para atender a esses pacientes 4,8,9 . Os modelos mais significativos surgiram na Inglaterra, na França e nos Estados Unidos.…”
Section: A Reforma Da Assistência Psiquiátricaunclassified